(untitled) (Third Sector Social Economic Review, 2018)
The civil society that its importance increasing day after day can be defined as that it is not under the coercion and control of the state, and aims to find an effective solution to social problems by organizing its actions through voluntarily. In developed countries, civil society organizations are seen as a driving force in society, in terms of subject in Turkey it is seen that the number of civil society organizations is much, but it is not at the efficiency level that should be the quality. Referring to Turkey in the study of civil society organizations on migration, the importance of the activities carried out by these organizations is understood more, because of geographical position that Turkey as a transit or destination country for immigrants. In order to go to Europe, Turkey encounter with a legal/illegal continuous migration from the own’s east countries, and has come face to face with a serious immigrant wave especially after the civil war that started in Syria in 2011.Turkey is trying to find a solution in this problem area through both the government and a limited number of civil society organizations. The insufficiency of the presumption of civil society organizations in Turkey, in this study first a conceptual discussion of the topic then the activities of these limited number of institutions, the areas they are in and their limitations will be tried to examine.